Gene Polymorphism of Antigen B Subunit 2 and Pathogenesis of Cystic Echinococcosis in Murine Model - Hadi M. Alsakee; Hussein M. Abdulla; Reshna K. Albarzanji (ARO-The Scientific Journal of Koya University)
A complex genetic diversity among the causative agent, Echinococcus granulosus, is documented. Antigen B (AgB) is a major antigenic fraction of hydatid fluid and hydatid cyst tissues. This study aims to investigate the role of antigen B subunit 2 (AgB2) gene polymorphism in the pathogenesis of cystic echinococcosis (CE) in murine model. Ovine liver hydatid cysts are obtained from Erbil Slaughterhouse. Protoscoleces from each isolate are separated into two batches. First preserved at −20°C for molecular analysis whereas the second is used for experimental infection in mice. Parasite DNA was extracted, and AgB2 genome was amplified and sequenced. The sequencing profile of six of the isolates (1, 2, 3, 5, 8, and 11) revealed a 100% analogy with AgB2 gene of E. granulosus genotype G2. Minor sequence polymorphisms, 1.67%, are observed in one of the isolates, whereas remarkable DNA sequence polymorphisms are noticed in three of the isolates. The polymerase chain reaction (PCR) products sequencing profiles revealed 100% polymorphisms in four of the isolates in comparison with the source gene (AY569356.1), instead, those isolates reveal various degrees of analogy, 80.33%, 80.87–89.05%, and 89.36% to G1, G3, and G6, respectively. Polymorphic sequencing profile of the PCR-amplified product (250 bp) of E. granulosus clone EgB2G2v13 AgB2 gene (Accession no.: AY569356.1) has no significant impact on the pathogenicity of the CE in murine model. To upgrade the diagnostic sensitivity rates of the immunological techniques, a mixture of native hydatid antigens containing AgB is recommended to be used in the ser-diagnosis of this infection.